Comparative analysis of jujube and sour jujube gave insight into their difference in genetic diversity and suitable habitat - Shao, Lingzhi; Qiao, Ping; Wang, Jingyi; Peng, Yanfang; Wang, Yiheng; Dong, Wenpan; Li, Jie (Frontiers in Genetics, 2024)
Jujube (Ziziphus jujuba var. jujuba Mill.) and sour jujube (Z. jujuba var. spinosa (Bunge) Hu ex H.F.Chow.) are economically, nutritionally, and ecologically significant members of the Rhamnaceae family. Despite their importance, insufficient research on their genetics and habitats has impeded effective conservation and utilization. To address this knowledge gap, we conducted plastome sequencing, integrated distribution data from China, and assessed genetic diversity and suitable habitat. The plastomes of both species exhibited high conservation and low genetic diversity. A new-found 23 bp species-specific Indel in the petL-petG enabled us to develop a rapid Indel-based identification marker for species discrimination. Phylogenetic analysis and dating illuminated their genetic relationship, showing speciation occurred 6.9 million years ago, in a period of dramatic global temperature fluctuations. Substantial variations in suitable climatic conditions were observed, with the mean temperature of the coldest quarter as the primary factor influencing distributions (-3.16 to 12.73 ℃ for jujube and -5.79 to 4.11 ℃ for sour jujube, suitability exceeding 0.6). Consequently, distinct conservation strategies are warranted due to differences in suitable habitats, with jujube having a broader distribution and sour jujube concentrated in Northern China. In conclusion, disparate habitats and climatic factors necessitate tailored conservation approaches. Comparing genetic diversity and developing rapid species-specific primers will further enhance the sustainable utilization of these valuable species.